2019
DOI: 10.17675/2305-6894-2019-8-3-13
|View full text |Cite
|
Sign up to set email alerts
|

Green approach in anti-corrosion coating by using Andrographis paniculata leaves extract as additives of stainless steel 316L in seawater

Abstract: The analysis of anticorrosion coating by using Andrographis paniculata (kalmegh) leaves extract (KLE) as an additive to protect stainless steel 316L that immersed in seawater environment was successfully carried out. The anti-corrosive coating is the combination of selected binder, pigment, solvent, and additive. Andrographis paniculata leaves extract was selected as an additive due to excellent antioxidant properties. There are five types of coating with different concentration which are C1 (0 wt.%), C2 (3 wt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Optical absorption studies are crucial in identifying an appropriate photocatalyst for light-driven pollutant degradation, which requires an adequate number of photons to be captured by the activity center [ [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. UV–Vis spectrophotometry was utilized to determine the optical absorption of the present samples.…”
Section: Resultsmentioning
confidence: 99%
“…Optical absorption studies are crucial in identifying an appropriate photocatalyst for light-driven pollutant degradation, which requires an adequate number of photons to be captured by the activity center [ [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. UV–Vis spectrophotometry was utilized to determine the optical absorption of the present samples.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic additives (organic UV absorbers (UVAs) and inorganic metal oxide nanoparticles like CeO 2 and ZnO) are incorporated in coatings to protect wood from weathering degradation. However, the leaching out of inorganic nanoparticles remains a major issue . They provide outstanding coating characteristics and improve substrate protection. , However, these synthetic organic and inorganic additives are primarily hazardous to human health and nature. The emission of volatile organic compounds (VOCs) from synthetic coatings too raises concern about their usage .…”
Section: Introductionmentioning
confidence: 99%
“…9 They provide outstanding coating characteristics and improve substrate protection. 10,11 However, these synthetic organic and inorganic additives are primarily hazardous to human health and nature. The emission of volatile organic compounds (VOCs) from synthetic coatings too raises concern about their usage.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, KLE was also found out to be a mixed type inhibition with a dominant cathodic effect [20]. As a component in a coating, a research suggested that the incorporation of KLE as an additive yields a significant increase in coating performance when it is used up to 6 wt.%, and further addition caused a significant drop in the barrier quality [21].…”
Section: Introductionmentioning
confidence: 99%